THE IMPLEMENTATION OF TECHNOLOGICAL BASED SUPERVISION TOWARD TEACHERS IN MALANG REGENCY - Fajri, Taufik Akbar Al; Andarwulan, Trisna (Erudio Journal of Educational Innovation, 2025)
This study investigates the implementation of technology-based supervision in Malang Regency, focusing on its challenges and opportunities. Utilizing a descriptive quantitative research design, data were collected from 200 teachers using a questionnaire based on the Technology Acceptance Model (TAM) and the Unified Theory of Acceptance and Use of Technology (UTAUT). The findings reveal high levels of technology acceptance, with most teachers finding the tools easy to use and beneficial for enhancing their performance. However, varying levels of technical support availability highlight the need for more consistent and accessible support structures. The study also underscores the significant positive impact of technology-based supervision on educational quality, supported by theoretical frameworks such as the Extended Technology Acceptance Model, Task-Technology Fit Theory, and Resource-Based View. To further improve implementation, the study suggests enhancing technical support, providing comprehensive training, and improving communication channels. These measures aim to ensure broader and more effective adoption of technology-based supervision across all schools.